2020
DOI: 10.7717/peerj.8084
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the proverb ‘more haste, less speed’: classic versus metabarcoding approaches for the diet study of a remote island endemic gecko

Abstract: Dietary studies can reveal valuable information on how species exploit their habitats and are of particular importance for insular endemics conservation as these species present higher risk of extinction. Reptiles are often neglected in island systems, principally the ones inhabiting remote areas, therefore little is known on their ecological networks. The Selvagens gecko Tarentola (boettgeri) bischoffi, endemic to the remote and integral reserve of Selvagens Archipelago, is classified as Vulnerable by the Por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…An alternative explanation for the absence of vertebrates could be due to the small sample size and technical limitations, such as the lack of power of the 12S primers to amplify the highly degraded DNA of our samples. However, these markers have been effectively used to amplify museum samples [ 98 ] and were used in a variety of dietary studies with successful results [ 68 , 99 ]. Moreover, the other markers worked very well on these samples despite being more than 100 years old and possibly poorly preserved for DNA amplification.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for the absence of vertebrates could be due to the small sample size and technical limitations, such as the lack of power of the 12S primers to amplify the highly degraded DNA of our samples. However, these markers have been effectively used to amplify museum samples [ 98 ] and were used in a variety of dietary studies with successful results [ 68 , 99 ]. Moreover, the other markers worked very well on these samples despite being more than 100 years old and possibly poorly preserved for DNA amplification.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the trophic niches of many lizard species have not been defined, partly due to challenges in identifying prey taxa in fecal pellets (Pereira et al, 2019 ). DNA metabarcoding of fecal samples can identify prey at a high taxonomic resolution and reveal previously unknown aspects of species diet (Gil et al, 2020 ; Jarman et al, 2013 ; Lopes et al, 2019 ). Using DNA metabarcoding, Pinho et al ( 2018 ) showed that the Endangered giant wall gecko ( Tarentola gigas ) predates one of the world's rarest bird species, the Raso lark ( Alauda razae ) in the Capo Verde Archipelago off the west coast of Africa.…”
Section: Use Of Edna In Dietary Analysismentioning
confidence: 99%
“…Not only was predation occurring, the Raso lark was the most frequent vertebrate signature found in the gecko's feces (Lopes et al, 2019 ), creating an interesting conservation dilemma in relation to management of these two threatened species. In another study, Gil et al ( 2020 ) used DNA metabarcoding to show that a gecko previously assumed to be insectivorous, was actually a generalist. This resulted in a greater understanding of its role in the ecological network (Gil et al, 2020 ).…”
Section: Use Of Edna In Dietary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study based on morphological examination of stomach contents revealed the presence of only a few soft-bodied prey items, such as nematodes [20]. Indeed, traditional diet methods tend to underestimate the frequency of occurrence of prey items with totally digested body parts, such as soft-bodied arthropods [24], while these methods tend to more easily detect hard-bodied groups [25]. Although it has been shown that the prey's DNA is recoverable from seahorse feces [15], there have been no published studies demonstrating the use of highly sensitive and non-invasive molecular techniques to evaluate the entire spectrum of seahorses' dietary items despite the sensitive conservation status.…”
Section: Introductionmentioning
confidence: 99%